The role of dietary fat in anti-tumour immunity - Prendeville, Hannah Catherine (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Obesity increases the risk of many cancers and impairs immunosurveillance. However, little is known about whether the type of dietary fat affects tumour growth and anti-tumour immune responses. Here, we show that a high-fat diet (HFD) from animal sources (lard or butter), but not plant sources (palm, coconut, peanut oil) accelerates tumour growth, despite similar levels of obesity and adipose distribution. Animal-derived HFDs impaired NK and CD8 T cell metabolism by two distinct cell specific mechanisms, both leading to mitochondrial dysfunction and loss of IFNγ production. The animal derived butter versus plant derived palm oil yielded the most different results and were used to investigate the mechanism in depth. Butter fed mice had significantly accelerated tumour growth while palm fed mice were completely protected from obesity-induced tumour progression despite equal obesity. Using in vivo whole body metabolic analysis and multiomic profiling, we found that HFDs caused a systemic metabolic switch to β-oxidation and impaired glucose handling regardless of fat source. However, at the metabolome level, critical differences were revealed which impacted tumour growth and immunity. Animal fat, but not plant fat, caused accumulation of intracellular lipids in NK cells, increased reactive oxygen species, metabolic paralysis, and impaired IFNγ production. However, in plant derived HFDs, NK cells activated antioxidant pathways involving Nrf1 and Nnt, protecting from lipotoxicity and retaining cytotoxic function despite obesity. Furthermore, animal derived HFDs result in incomplete fatty acid oxidation in key metabolic organs, causing systemic accumulation of circulating long chain acylcarnitines, particularly octadecanoyl-carnitine which completely impaired CD8 T cell metabolism and function. Weight loss restored the plasma metabolome and peripheral NK and CD8 T cell functional responses, however, did not protect against tumour growth and tumoral NK and CD8 T cells were still defective. These data reveal that excess dietary fat from animal sources is more harmful to anti-tumour immunity and these functional defects persist after weight loss. This may inform the nutritional regime for patients alongside traditional cancer therapies, particularly immunotherapy.
APPROVED
Keywords: Obesity, lipids, cancer, immunometabolism, NK cells, CD8 T cells